Effectiveness of cryolipolysis for subcutaneous fat reduction: a systematic review and meta-analysis - Guilherme Aron Teixeira Silva; Daysiane Rocha Souza; Karina Emburana Costa Parreiras; Janaíne Cunha Polese; Fernanda Souza da Silva (Sociedade Brasileira de Dermatologia (SBD), 2021)
Introduction: Cryolipolysis produces selective, controlled cooling, and it's based on the concept that lipid-rich tissue is more susceptible to cold injury, reducing subcutaneous fat. Objective: To review the literature to assess the effectiveness of cryolipolysis in reducing subcutaneous fat. Methods: Systematic review with meta-analysis of studies published in the EBSCOhost, LILACS, and PUBMED databases. Results: Only one study did not present significant reduction in subcutaneous fat compared to the control group.There was a difference among the parameters in the studies. Conclusion: Cryolipolysis is an effective tool for localized fat reduction.